Descartes: Moral philosopher - Morales Guerrero, Julio (Estudios de Filosofía, 2017)
Descartes is on science with a practical aim not a theoretical one; for this reason he is a moral philosopher rather than speculative. His moral philosophy was just one; and as his moral is perfectible, he expresses it as provisions for those who travel through life, in his book Discourse on the Method. This moral takes the form of ethics of generosity in the Passions of the Soul, when one has the feeling to dominate freedom and has the resolution to use it well, and never lose it. He introduces a distinction between “morally certain” and “more than morally certain” which refers to the guarantee of the truth, not to tenuous truth that we apply in daily life or to solid truth that we apply to theorize.